Da'wah Communication Strategy on the TikTok Account "Qur'an GPT” - Muhammad Akbar Febriansyah Akbar; Nashihin Sumarjan; Hadi Ismanto (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
his study uses a qualitative research method with the theory of Da'wah Strategy which classifies into three forms of da'wah communication strategies, namely: 1) Rational Strategy, 2) Sensory Strategy, 3) Sentimental Strategy. The focus of this study is on da'wah communication strategies and supporting and inhibiting factors. From the results of the analysis of each da'wah video made by the TikTok account "Qur'an GPT", the researcher got the results, 1) Of the 141 da'wah videos made by the TikTok account "Qur'an GPT" using three forms of da'wah communication strategies, there are 80 videos with the application of Rational Strategy, 9 videos with the application of Sensory Strategy, and 52 videos with the application of Sentimental Strategy. 2) Factors that support and inhibit the da'wah activities carried out by the TikTok account "Qur'an GPT" on social media, both in terms of the da'wah communication strategy used such as the characteristics of the TikTok account "Qur'an GPT" which is a combination of the Qur'an and Artificial Intelligence, as well as from the selection of TikTok social media, so that it can be known what the problems or obstacles are and solutions can be found to these problems.